Carvão ativado de casca de maracujá como adsorvente alternativo na remoção de corantes alimentícios sintéticos em solução aquosa mono e multicomponente - Cabral, Lucas Lacerda (2022)
A considerable portion of synthetic dyes is discarded in water bodies due to the large amount used in the industrial process, and the toxicity of these compounds is harmful to the aquatic community. Adsorption has been investigated as an efficient treatment process for these pollutants, combined with the use of alternative adsorbents. Passion fruit, a fruit widely produced and consumed in Brazil, has the peel as its main residue, with great potential for reuse as an adsorbent. Thus, the objective of this work was to evaluate the application of an activated carbon produced from passion fruit peel (PFAC) as an alternative adsorbent in the removal of synthetic food dyes indigotine blue (IB), tartrazine yellow (TY) and ponceau 4R (P4R) in mono and multicomponent aqueous solution. The adsorbent was physical-chemically and texturally characterized. Removal efficiency was optimized by factorial experimental design with central composite rotational design (CCRD) 22, to investigate the influence of adsorbent dosage (D) and temperature (T) on dye adsorption. Kinetic assays were performed to obtain the equilibrium time, with fitting of the experimental data to Lagergren pseudo-first-order, Ho-McKay pseudo-second-order and Elovich models. Equilibrium isotherm assays were conducted and the data fitted to Freundlich, Langmuir, Sips, Temkin and Redlich-Peterson models. Thermodynamic assays were performed at temperatures of 25, 40 and 55 ºC to determine enthalpy (ΔHº), entropy (ΔSº) and Gibbs energy (ΔGº) variations. Assays in binary and ternary solutions were conducted to investigate the competitiveness of dyes for available sites in the adsorbent. In the optimal conditions obtained in the planning, synthetic effluents containing the dyes were treated. The adsorbent presented macroporous characteristics, small surface area (0.08 m2 g-1), alkaline pH (10.90) and predominance of basic groups by the Boehm method (0.56 mmol g-1). By the CCRD, higher removal efficiency was verified for IB (100%) in D = 8.8 g L-1 and T = 45.3 ºC, for TY (79%) in D = 9.6 g L-1 and T = 52.5 °C and for P4R (84%) at D = 8.7 g L-1 and T =52.9 °C. The experimental data were better fitted by the Elovich kinetic model (R2 > 0.98) and the Redlich-Peterson isotherm model (R2 > 0.99), both advocating the influence of chemical processes on adsorption. The thermodynamic results denoted an endothermic process (ΔHº > 0), with a high degree of randomness of the molecules (ΔSº > 0) and spontaneous (ΔGº < 0). In the multicomponent solutions, antagonistic effects of interaction between the dyes were noticed, in which the presence of one adsorbate suppressed the adsorption of the other, leading to smaller amounts adsorbed in comparison to the single component assays. Mechanism studies indicated the occurrence of adsorption by pore-filling, electrostatic attraction, hydrogen bonding, π-π interaction and covalent bond formation. The application of PFAC in the treatment of synthetic effluents showed promising results with good removal efficiencies for IB (99.87%), TY (52.51%) and P4R (67.90%). Therefore, it was possible to verify the potential application of PFAC as an alternative adsorbent for food coloring, based on the results obtained in this work.